Epidemiological Characterization of Patients with Intestinal Stomas - Carneiro, Liliane Moretti; Ferreira, Adriano Menis; Rigotti, Marcelo Alessandro; Sokem, Jaqueline Aparecida dos Santos; Giroti, Alessandra Lyrio Barbosa; Serra, Rodrigo Aranda; Diniz, Maiara Oliveira (Journal of Coloproctology, 2023)
Objective To characterize the sociodemographic and clinical variables of people with intestinal stomas.Materials and Methods We conducted a cross-sectional study with 47 patients of a Specialized Rehabilitation Center (CER II/APAE) in the municipality of Três Lagoas, state of Mato Grosso do Sul, Midwestern Brazil, from December 2019 to June 2020. Data was analyzed using inferential descriptive statistics (Anderson-Darling, Chi-squared, and Mann-Whitney normality tests).Results Regarding the patients, 87.23% were from Três Lagoas, 51.06% were female, 40.43% were aged from 60 to 69 years, 59.57% were married, 53.19% were brown, 59.57% were catholic, 36.17% finished elementary school, 46.81% were retired, and 57.45% earned a monthly income below 1 minimum wage. Moreover, 61.70% had undergone terminal colostomy (61.70%), 61.70% had received guidance about its placing, 57.45% had it placed due to situations of urgency, 74.47% had a stoma installed due to a neoplasia, 38.30% were permanent, with 46.81% located in the inferior left quadrant (ILQ), 59.57% presented pasty effluent, 63.83% had a circular diameter, 53.19% had pouches with 2 pieces and 57.45%, with a flexible base, 87.23% had other adjunct equipment, and 95.74% had been trained in self-care. The most common complication was skin/peristomal irritant contact dermatitis (59,57%), and 65,95% of these cases were solved by teaching self-care. The type of stoma was significantly associated with the consistency of the effluent and the size of the protrusion (p > 0.05).Conclusion The results found can support strategies to implement practices to promote health, develop new public policies, to provide training in self-care, and prevent and treat complications.
Keywords: ostomy; intestinal elimination; health profile; self-care